Critical Geographies (A Collection of Readings) Two Decades On: A Conversation with Harald Bauder and Salvatore Engel-Di Mauro - Anderson, Christian (ACME, 2025)
In this conversation, Harald Bauder and Salvatore Engel-Di Mauro reflect on Critical Geographies: A Collection of Readings—an open access collection published in 2008 by Praxis (e)Press, which was then the book publishing arm of ACME. Bauder and Engel-Di Mauro begin by reflecting on their experiences editing and releasing the collection, situating these experiences in relation to conditions of academic knowledge production and shifting formations of critical and radical geography at the time. Consideration of those conditions and formations then remain central throughout the conversation, which further interweaves broader discussions of pedagogy, competing notions of impact, the politics of publication and citation, and more.